STRATEGI GURU DALAM MENGGUNAKAN METODE EVERYONE IS A TEACHER HERE DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP ISLAM AL-AWWAL PALEMBANG - Fatonah, Sofhiatul; Rahmadani, Nia; Fauzi, Muhamad; Wulandari, Widya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe teachers’ strategies in using the Everyone Is a Teacher Here method to improve students’ learning outcomes in Islamic Religious Education (PAI) at SMP Islam Al-Awwal Palembang. This research employed a qualitative method with a descriptive approach. The data sources consisted of primary data obtained through observations and interviews with teachers and students, while secondary data were obtained through literature studies. Data collection techniques included observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that the teacher’s strategy in implementing the Everyone Is a Teacher Here method was carried out by first providing an understanding of the material, then actively involving students through questioning, answering, and class presentations. This method was able to increase students’ activeness, self-confidence, and understanding of PAI material, both theoretically and practically. The implementation of the method was also supported by learning media such as videos, pictures, and direct practice, making the learning process more interesting and less monotonous. However, several obstacles were found, including limited time, differences in students’ abilities, low self-confidence among some students, and difficulties in formulating appropriate questions. To overcome these obstacles, teachers provided material reinforcement, continuous evaluation, and direct guidance outside the classroom.